PECULIARITY OF LEADERSHIP IN STAKEHOLDER INTERACTION MANAGEMENT IN SUSTAINABLE DEVELOPMENT PROJECTS OF ENTREPRENEURIAL STRUCTURES - KHOMYCH, LILIIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the specificity of leadership in stakeholder interaction management in implementation of sustainable development projects and highlights that large-scale and complexity of the execution of relevant development projects has needs for effective leadership, which is able not only to form an attractive future model, but also to involve all actors in the realization of plans. This paper characterizes the specifics of the motivational function of leadership in working with interested persons and argues that it is important to ensure the effectiveness of stakeholder interaction in the implementation of development projects. I use my own interpretation of the term "motivational potential of a leader" in relation to work with stakeholders. I emphasize the necessity of adequate methodological substantiation of ways of positioning different groups of interested persons in the environment of enterprise activity. I propose my authorial scientific approach for the company stakeholder positions on the strength of their effect and place on decision-making concerning sustainable development projects. The research underscores that understanding the strength of the impact of different stakeholder groups on decision-making allows management to reasonably defend the company position in the negotiation process with representatives of each group, choosing valence ways to satisfy the interests of those who can be most useful at every stage of development projects.
Keywords: sustainable development; innovative-technological transition; stakeholder power of influence; motivational potential of a leader; enterprise